Dil- Zihin İlişkisi Çerçevesinde Metaforlar - ŞERİFOĞLU, Yasin (Abant Izzet Baysal University Graduate School of Social Sciences, 2012)
An absolute relationship between place (geography), society (culture), human, mind, and language can be described as one of the most functional systems, perhaps the most important one. Human, who learns and experiences thanks to this multifaceted relationship, transmits these experiences to the interlocutor or the successors through language which is a product of this relationship. The meanings attributed to the words in these transmissions and the new relationship between these meanings with others concepts, other words and their meanings could come up as the result of the unique function of human mind. In this work, after the short story of language-mind relationship is evaluated, the genesis form of language with it’s every aspects, is tried to be explained. The basic elements in forming language are put forward in this expression, it is tried to be elucidated what is metaphor, how it is; depending on these elements. Also the opinions that are related with formation ways of sayings in the language, are discussed in this part. Consequently, it is expressed that the big part of new namings in the language is mental, so it is emphasized that human mind performs to name the new ones by comparing with the things that it has seen before, i.e. by associating/ comparing with the things which it has experienced or transfering from one or a few of them.